A Survey on Multi-User Conversational Interfaces - Nicolas Wagner; Matthias Kraus; Wolfgang Minker; David Griol; Zoraida Callejas (Applied Sciences, 2025)
This paper investigates the evolving landscape of Multi-User Conversational Interfaces, addressing the limitations of traditional systems that primarily focus on single-user interactions. As real-world applications grow more complex, there is a pressing need for conversational systems capable of facilitating dialogues among multiple participants. Our systematic survey reviews recent advancements in the field, highlighting innovative architectures, application domains, user and dialogue modelling, and evaluation metrics tailored for multi-user contexts. We conduct a comprehensive analysis of relevant literature, employing both quantitative and qualitative methodologies to identify common patterns and challenges in multi-user interactions. The findings underscore the importance of developing robust interfaces that can effectively manage overlapping dialogues, ensure collaborative group work, and enhance overall conversational quality. This work contributes to the understanding of Multi-User Conversational Interfaces and may help as a basis for future research aiming to develop more natural, user-friendly, and effective conversational interfaces.